Genotype plus Genotype by Environment Interaction (GGE) Biplot Analysis of Nutrient Quality Traits in Rice (Oryza sativa L.) (2013)
This paper reports analysis of a 7 x 7 diallel crosses using genotype main effect (G) plus genotype-by-environment (GE). interaction (GGE) biplot to determine nutrient quality traits in rice. Analysis of variance indicate significant differences between genotypes, general combining ability and specific combining ability for all of the traits. The hybrid Sepidrod x Neda had the highest mid parent heterosis (MPH) for protein content and Potassium (K). The graphical representation by biplot analysis allowed a rapid and effective overview of general combining ability (GCA) and revealed that Shahpasand was an ideal general combiner for protein content, Phosphorus (P), Zinc (Zn) and Manganese (Mn); whereas Sepidrod was a poor general combiner for P, K and Zn. Three landraces containing Shahpasand, Deilmani and Hassani was the best general combiners for protein content.The estimate of specific combining ability (SCA) effects indicated Shahpasand as a good parent for improving protein content. According to SCA effects of parent and biplot polygon view, crosses Hassani x Sepidrod and Neda x Sepidrod exhibited the highest level of protein content and significant heterosis. The best crosses for improving K content was Shahpasand x Deilmani and Neda x Sepidrod. Sepidrod x IRFAON-215 and Deilmani x IRFAON-215 were the best crosses for improving Iron (Fe) content. On the other hand, Sepidrod x IRFAON-215, Deilmani x IRFAON-215 also were the best crosses and in improving Zn and Mn content. Then information obtained from this experiment can facilitate the identification of hybrids that are best combined for improved nutrient quality traits in rice.